S81 A randomised controlled study comparing the outcomes of pleural nurse practitioner versus doctors trained to perform pleural procedures for management of pleural effusions. (14th November 2013) - Reid, ER; Sivasothy, PR; Chatterji, S
Abstract : Background: Following the National Patient Safety Agency alert in the UK thoracic ultrasound (TUS) is strongly recommended for all pleural procedures. This places strains on clinical service delivery. The role of the Nurse Practitioner (NP) in this setting is not established. We undertook a randomised control study to test the hypothesis that a Nurse Practitioner trained to Royal College of Radiologist level 1 TUS and in performing pleural procedures independently is equivalent to doctors trained in undertaking pleural procedures. Method: In this prospective ethically approved un-blinded non-inferiority study we assessed pleural procedures as carried out by a Nurse Practitioner (Group A) in comparison with doctors trained in pleural procedures (Group B) in 32 patients. Primary endpoints were success of the pleural procedure, procedural pain using visual analogue score (VAS), patient anxiety using short form State Trait Anxiety Index (STAI). Secondary outcome measures were complications. Non parametric statistical tests were used for analysis. Results: There was no statistically significant (NS) difference between groups as assessed by primary endpoints (Table 1). There was one failure to undertake therapeutic pleural aspiration in Group B. Delayed complications were drain dislodgement in Group A and re-expansion pulmonary oedema in Group B. Conclusion: We believe this is the first randomised control study to test if after appropriate training a Pleural Nurse Practitioner is able to safely and effectively undertake pleural procedures with equivalence in practice to trained doctors.